A Protocol for Improving Loneliness in People with Multiple Sclerosis. (2nd April 2016) - Kalina, Jennifer Tamar; Hinojosa, Jim
ABSTRACT: Loneliness is a subjective and unpleasant emotional state that occurs when people feel social networks or social relationships are deficient in some way. People with multiple sclerosis are often lonely and frequently withdraw from participating in meaningful social activities. Common symptoms, such as cognitive changes, decreased physical functioning, fatigue, incontinence, visual changes, or depression, may contribute to decreased social participation, which can lead to loneliness. This article presents an intervention protocol for improving loneliness in people with multiple sclerosis. This protocol is based on Bandura's Social Learning Theory, which focuses on improving self-efficacy to reduce loneliness in people with multiple sclerosis.